PENILAIAN RISIKO JATUH DENGAN PENGGUNAAN TIMED UP AND GO TEST PADA PENDERITA OSTEOARTHRITIS GENU GRADE 1 - 3 - Humaryanto, Humaryanto; Tobing, Maudy Rominar Br (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
ABSTRACT Background: Knee osteoarthritis (OA) is the most common form of arthritis. The presence of knee pain, decreased functional mobility, stiffness, and decreased quadriceps strength in knee OA patients can cause physical disability. In optimizing the patient's functional mobility to perform activities of daily living, a valid and reliable tool is needed at the beginning and after the intervention. The purpose of this study was to measure functional mobility by assessing the risk of falling using the TUG test in patients with knee OA grade 1 to grade 3. Methods: A descriptive study with 93 samples of knee OA patients at the Orthopedic Surgery Clinic of the hospital. Data were obtained from interviews, medical records, and observation sheets. Results: Based on age, knee OA was most common in patients in the late elderly group, namely 45 patients (48.4%). Based on gender, knee OA is more common in women (84%) than men (16,1%). Based on Body Mass Index (BMI), the results of a normal BMI are the same as those of heavy fat (42%). From the radiological examination results, patients with genu OA were at K/L 2 degrees as many as 46 patients (49.4%). On the TUG test results, knee OA patients with a low risk of falling were 68 patients (73.1%). Knee OA patients who have a low risk of falling are more experienced by knee OA patients with BMI in the heavy fat category, namely 28 patients (30.1%). Patients with grade K/L 1 had the lowest fall risk as many as 17 patients (85%), patients with K/L 2 degrees had the lowest risk of falling as many as 38 patients (83%), patients with K/L 3 degrees had low fall risk equals moderate fall risk in 13 patients (48%). Conclusion: Knee OA patients both at grade 1, grade 2, and grade 3 have the lowest risk of falling and all knee OA patients have the risk of fallers due to their OA. Keywords: knee osteoarthritis, TUG test, Kellgren-Lawrence